Lysosomal damage promotes autophagy-based unconventional secretion of the Parkinson’s disease protein PARK7 - Biplab Kumar Dash; Yasuomi Urano; Noriko Noguchi (Redox Experimental Medicine)
Objective: PARK7/DJ-1 is a multifunctional protein and redox sensor essential for cellular survival and oxidative stress defense. PARK7 secretion is linked to pathophysiologies, including neurodegenerative diseases, cancer and inflammation. This study investigates the mechanisms of PARK7 secretion in response to lysosomal membrane permeabilization induced by L-leucyl-L-leucine methyl ester (LLOMe). Methods: HeLa and mouse embryonic fibroblasts cells were treated with LLOMe followed by washout with serum-free Dulbecco’s modified Eagle’s medium. PARK7 secretion was analyzed by assessing the intracellular and extracellular protein levels. Results: Upon LLOMe treatment, PARK7 translocates to damaged lysosomes, colocalizing with galectin-3 (LGALS3), a marker of lysosomal damage. Following LLOMe washout, an increase in lysophagy flux was observed, enhancing the secretion of both PARK7 and LGALS3. The knockdown of TANK-binding kinase 1, a critical lysophagy regulator, suppresses LLOMe-induced PARK7 secretion, confirming a lysophagy-dependent mechanism. Notably, while the inhibition of autophagy initiation blocks PARK7 secretion, the disruption of autophagosome–lysosome fusion does not affect its release. In addition, the SEC22B-mediated SNARE complex, comprising STX3/4 and SNAP23/29, is essential for the fusion of secretory autophagosomes with the plasma membrane during PARK7 secretion. Conclusion: These findings reveal a novel lysophagy-dependent mechanism of PARK7 secretion, where acute lysosomal damage facilitates the recruitment of PARK7 to damaged lysosomes, subsequent autophagosome encapsulation and nondegradative release into the extracellular space through a dedicated SNARE complex. Significance statement: The findings of this study broaden the understanding of unconventional protein secretion under lysosomal stress and highlight the potential therapeutic targets for diseases linked to lysosomal dysfunction, including neurodegeneration and inflammation.